Post-Snowden internet policy: between public outrage, resistance and policy change - Julia Pohle; Leo Van Audenhove (Media and Communication, 2017)
This editors' introduction provides a short summary of the Snowden revelations and the paradoxical political and public responses to them. It further provides an overview of the current academic debate triggered by the Snowden case and the documents leaked by him and introduces the articles featured in this issue on post-Snowden Internet policy.
Additional information: The publication of this article was funded by the Open Access fund of the Leibniz Association. This article is part of the issue “Post-Snowden Internet Policy”, edited by Julia Pohle (WZB Berlin Social Science Center,Germany) and Leo Van Audenhove (Vrije Universiteit Brussel, Belgium).
Keywords: 330; digital; intelligence agency; Internet policy; policy change; privacy; Snowden; surveillance; whistleblowing